Enhancing Outcomes in Opioid Use Disorder Treatment: An Economic Evaluation of Improving Medication Adherence for Buprenorphine Through Blister-Packaging - Borrelli EP; Saad P; Barnes NE; Nelkin H; Dumitru D; Lucaci JD (Dove Medical Press, 2024)
Eric P Borrelli,1 Peter Saad,2 Nathan E Barnes,2 Heather Nelkin,3 Doina Dumitru,3 Julia D Lucaci4 1Health Economics & Outcomes Research; Becton, Dickinson and Company, San Diego, CA, USA; 2Medical Affairs; Becton, Dickinson and Company, Durham, NC, USA; 3Medical Affairs; Becton, Dickinson and Company, San Diego, CA, USA; 4Health Economics & Outcomes Research; Becton, Dickinson and Company, Franklin Lakes, NJ, USACorrespondence: Eric P Borrelli, Becton, Dickinson and Company, 3750 Torrey View Ct, San Diego, CA, 92130, USA, Email Eric.Borrelli@bd.comBackground: The opioid epidemic has severely impacted the US over the last 15 years. Buprenorphine is a partial opioid agonist indicated for the treatment of opioid use disorder (OUD) and is recognized as an effective treatment when taken as prescribed. However, adherence rates have been low in real-world settings. Blister-packaging has been shown to promote medication adherence across a variety of disease states, although it has never been studied in OUD.Methods: An economic analysis was conducted to assess the impact of increased adherence of blister-packaged buprenorphine on health care resource utilization (HCRU) and health care costs for 10,000 patients initiating therapy for OUD. The model analyzed a commercially insured population within the US over a one-year time horizon. Medication adherence was defined in the model as proportion of days covered (PDC) of at least 80%. Literature-based references were used to inform both the impact of blister-packaging on the number of patients who became adherent as well as the impact of medication adherence on HCRU and health care costs. Model input uncertainty was assessed in one-way sensitivity analyses.Results: With the implementation of blister-packaging buprenorphine, adherence rates increased from 37.1% of patients in the pre-intervention period to 45.3%, resulting in an additional 818 patients becoming adherent post-intervention. The increase in adherence led to a reduction of medical costs of $12,138,757 (-$1,214 per-patient (PP)). Specifically, inpatient costs decreased by $7,127,073 (-$713 PP) while outpatient costs decreased by $5,013,319 (-$501 PP). Pharmacy costs increased by $3,432,705 ($343 PP). Despite the increase in pharmacy costs, total health care costs saw a reduction of $8,559,684 (-$856 PP).Conclusion: Blister-packaging buprenorphine for treatment of OUD has potential to improve medication adherence and health outcomes while reducing HCRU and health care costs. Future studies are necessary to assess the real-world application and impact of blister-packaging buprenorphine for OUD across various patient populations and health care settings.Plain Language Summary: The opioid epidemic has taken its toll in the United States for the last several decades. Several medications are available in the treatment of opioid use disorder (OUD), including buprenorphine. Buprenorphine has shown to be an effective treatment when taken as prescribed, however, in real-world settings, the occurrence of patients taking buprenorphine as prescribed is low. Blister-packaging medications has been shown to help promote medication adherence across a variety of disease states, although it has never been studied in OUD. As a result, we attempted to model the potential impact that blister-packaging buprenorphine for 10,000 commercially insured patients initiating treatment for OUD would have on health care resource utilization and health care costs using the best available peer-reviewed literature. This analysis saw adherence rates increased from 37.1% of patients in the pre-blister-packaging period to 45.3% post-blister-packaging period, resulting in an additional 818 patients becoming adherent. The increase in adherence led to reductions of medical costs of $12,138,757 (-$1214 per-patient (PP)). Specifically, inpatient costs decreased by $7,127,073 (-$713 PP) while outpatient costs decreased by $5,013,319 (-$501 PP). Pharmacy costs increased by $3,432,705 ($343 PP). Despite the increase in pharmacy costs, total health care costs saw a reduction of $8,559,684 (-$856 PP). Future studies are necessary to assess the real-world application and impact of blister-packaging buprenorphine for OUD across various patient populations and health care settings.Keywords: blister-packaging, blister-packing, medication adherence, buprenorphine, health care costs, medication adherence packaging, opioid use disorder